Analisis faktor-faktor yang berpengaruh terhadap minat penggunaan e-commerce: Studi kasus di Shopee Indonesia - Kurniawan, Ricky Andi; Chendra, Mikhael; Kelvin, Kelvin; Anderson, Kevin; Yudianto, Wahyu (TEKNOLOGI: Jurnal Ilmiah Sistem Informasi, 2021)
The purpose of this study is to analyze the effect of perceived usefulness, perceived ease of use, risk, trust, and attitud e toward using on interest in using the Shopee application. The types that we use for research are qualitative and quantitative. This research was conducted with a number of respondents as many as 168 respondents. The sampling technique used was the cluster & stratified, dispropotional, random sampling technique. Hypothesis testing using multiple linear regression. The results showed that trust in conducting transactions and behavior in transactions can affect the interest in using the Shopee application in Batam city and other factors do not affect people's decisions in the city of Batam. The test results of the coefficient of determination on the adjusted R2 value show a value of 0.56 which means the independent variables in the study show a value of 56% and the other 44% is explained by the outside variables. This research can be a reference for readers in determining how to attract users to use or transact at Shopee in the city of Batam.